Effect of Eel Cookie Supplementation on the Hemoglobin Status of Pregnant Women with Anaemia: A Pilot Study - Dewi Marhaeni Diah Herawati; Deni Kurniadi Sunjaya; Lailia Fathul Janah; Nita Arisanti; Hadi Susiarno (International Journal of Food Science)
Background. Anaemia in pregnancy is a major global health problem. Iron and folic acid (IFAS) and animal-based supplement consumption could improve the hemoglobin status of pregnant women. This study is aimed at determining the effect of eel cookie supplementation on hemoglobin levels of pregnant women. Methods. This pilot study with pretest–posttest design was conducted in Tamanjaya Public Health Center, Geopark Ciletuh, Sukabumi District, West Java Province, Indonesia. A total of 40 voluntary pregnant women were divided into two groups: an intervention group that received 11 pieces of eel cookies and control group that received the same number of cookies without eel. The women’s hemoglobin level was analysed using t-test, Mann-Whitney, Wilcoxon, and analysis of covariance tests. Results. After consuming the eel cookies for 1 month, there was a significantly greater increase in the hemoglobin levels in the intervention group than those in the control group, which were 1.69 and 0.69 g/dL, respectively. Improvement in percentage of mean hemoglobin was higher in the intervention group than in the control group, which was 17.21% and 6.53%, respectively. Conclusions. Supplementation with eel cookies and IFAS for 1 month could improve the hemoglobin status in pregnant women with anaemia.